Realizing self-sustained biomass gasification in a lab-scale downdraft reactor for compact CHP applications - Takanori Itoh; Shota Hanabusa; Kazunori Iwabuchi (PLoS ONE, 2026)
Miniaturizing biomass gasifiers is key to enabling household-scale combined heat and power (CHP) systems integrated with solid oxide fuel cells (SOFCs), yet achieving self-sustained gasification at this scale is challenging due to severe heat losses. This study evaluates the self-sustaining potential of a lab-scale moving-bed downdraft gasifier using charcoal, across an equivalence ratio (ER) range of 0.47–0.65. Stable operation was achieved at ER = 0.47–0.60, with oxidation zone temperatures reaching 800–1000 °C. As ER increased, product gas performance improved, with CO and H 2 concentrations of 15% and 5% at ER = 0.60, yielding a lower heating value of 2.60 MJ/Nm 3 , carbon conversion efficiency of 74.4%, and cold gas efficiency of 48.4%. Performance remained below literature values, primarily due to limited reduction zone temperatures (~600 °C), likely caused by incomplete oxygen conversion (residual O 2 : 5.9%) and significant heat losses (~30.5%). Thermal analysis showed that reducing residual O 2 below 1% could theoretically raise temperatures by nearly 1000 °C. These findings demonstrate the feasibility of lab-scale autothermal gasification and identify oxygen utilization and thermal management as key levers for future ultra-small-scale CHP applications.